Bākaśāla ki ebaṃ kena? - Sāiẏida, Dilarubā (Muktibāṇī Prakāśanī, 1979)
On the background and objectives of the formation of Bāṃlādeśa Krshaka Śramika Āoẏāmī Līga (BAKSAL), political party system introduced by Shekh Mujibur Rahman, 1922-1975, former president of Bangladesh.